SKIS students excited to receive the UMP Foundation donation - Siti Nur Azwin, Zulkapri (2020)
Pekan, 26 August 2020 - Feelings of happiness and excitement radiated for 26 students with disabilities (OKU) who went to school at Sekolah Kebangsaan Indera Shahbandar (SKIS), Pekan when they received daily necessities donations from UMP Foundation.